Patient-based evidence: its role in decision making on end-of-life, orphan, and ultra-orphan medicines. (11th April 2023) - Hems, Sharon; Taylor, Louise; Jones, Jan; Holmes, Eileen
Abstract: Objectives: The Scottish Medicines Consortium (SMC) conducts early health technology assessment (HTA) of new medicines on behalf of NHSScotland. Assessment of end-of-life (EoL), orphan, and ultra-orphan medicines includes a process to gather evidence from patients and carers during Patient and Clinician Engagement (PACE) meetings. The output of PACE meetings is a consensus statement describing the medicine's added value from the perspective of patients/carers and clinicians. The PACE statement is used by SMC committee members in decision making. This study compared how PACE participants and SMC committee members rate the importance of information in PACE statements for these medicines. Methods: A survey was undertaken of patient group (PG) representatives and clinicians who participated in PACE meetings, and SMC committee members. Results: PACE participants who responded (26 PG representatives and 14 clinicians) rated health benefits and ability to take part in normal life as important/very important. Convenience of administration and treatment choice received the lowest rating. Hope for the future received the most diverse response. PACE participants generally rated the importance of quality of life themes higher than committee members ( n  = 20) but the rank order was similar. Differences between the proportion of PACE participants and committee members who rated themes as important/very important were greatest for treatment choice and hope for the future. Conclusions: In general, PACE themes and subthemes that were rated highly by PACE participants were also considered important by SMC committee members, indicating that information captured during PACE meetings is relevant when making decisions on EoL, orphan, and ultra-orphan medicines.